The Role of the “Private” in Inter-Gender Misunderstanding - Beran, Ondřej (Organon F, 2017)
In this paper, I use Wittgenstein’s private language argument for reflecting on some folk-linguistic misconceptions. In Section 1, I show that elements of the private language semantics inform common ways of looking at some situations referred to as “misunderstandings”. I suggest that it would be appropriate to conceive of the alleged misunderstandings as practical attitudes of mistreatment. This suggestion is explored in Section 2, which is devoted to a commonly assumed prominent example of the problem: the so-called inter-gender misunderstanding. It is believed that men and women use language in systematically different ways, as a result of which they do not understand each other properly, because they miss what their interlocutors “mean”. The conceptual apparatus of mentalist semantics presumed here is abused in order to advocate morally reprehensible actions against women. In Section 3, I suggest that the Wittgensteinian accounts of language and mind offer arguments for denying private conceptions of understanding on the grounds of both philosophy of language and ethics.
Keywords: gendered languages; misunderstanding; private language; sexual violence